Treatment of сongenital melanocytic nevus in infants and children by a dual-wavelengths copper vapor laser - Igor V. Ponomarev; Sergei B. Topchy; Alexandra E. Pushkareva; Yury N. Andrusenko; Ludmila D. Shakina (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
Introduction.Congenital melanocytic nevus (CMN) is detected at birth or shortly after birth in 1% of infants. The localization of CMN in aesthetically significant areas causes a decline in child self-esteem and causes concern for his parents. Surgical excision of skin areas with CMN is associated with an increased risk of cosmetic side effects and is often followed by long-term stress conditions after the invasive intervention. Aim of the study.To evaluate the efficacy of the CMN removal in infants, children and adolescents with the dual-wavelengths copper vapor laser (CVL) radiation. Patients and Methods.Medium-sized (up to 9 cm) single CMN was treated in nine fair-skinned patients: seven girls and two boys, aged from 2 months to 16 years. The procedures were carried out at an average CVL power of 0.61.0 W, with a power ratio of 3:2 at 511 nm and 578 nm wavelengths, and an exposure time of 0.20.3 s. Light spot diameter 1 mm. The treatment was carried out during 210 sessions with an interval of 12 months between sessions. Results.In children and adolescents, the treatment of CMN with CVL dual-wavelengths radiation made it possible to achieve significant clarification of the involved area without hypertrophic scars. The duration of the healing of the irradiated area lasted 23 weeks. Side effects were manifested with subtle skin atrophy. Conclusion.The high efficacy of CVL removal of medium-sized CMN in infants and children using the dual-wavelengths CVL radiation without pronounced side effects allows introducing such an approach in the clinical practice of pediatric dermatologists and cosmetologists.